APOE ε4‐independent pathways predominate in the association between retinal nerve fiber layer thinning and 12‐year incident dementia - Yuzhuo Wang; Xiaoxi Ma; Haoze Cen; Jie Wang; Jie Wu; Ding Ding; Yiqin Xiao; Qianhua Zhao (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2025)
Abstract INTRODUCTION Emerging evidence links retinal nerve fiber layer (RNFL) thinning to cognitive impairment, while the apolipoprotein E (APOE) ε4 allele, the key genetic dementia risk factor, is also found to be associated with RNFL thickness. This study investigated the longitudinal association between RNFL thinning and 12‐year dementia risk, evaluated the role of APOE ε4 in this relationship, and clarified the independent value of retinal imaging as a predictive biomarker for dementia. METHODS This study included 35,433 participants from the UK Biobank. Generalized linear models and Jonckheere‐Terpstra tests assessed the association between APOE ε4 allele dosage and macular RNFL (mRNFL) thickness. Cox models evaluated the association between mRNFL thickness and incident dementia. To address potential confounding by APOE ε4, inverse probability weighting was applied. Mediation analysis quantified the contribution of APOE pathways to the mRNFL‐dementia association. RESULTS Among 35,433 participants, 392 (1.11%) developed dementia over a median follow‐up of 12.49 years (interquartile range: 12.39 to 12.64). APOE ε4 carriers exhibited a dose‐dependent reduction in mRNFL thickness (β = −0.14, 95% confidence interval [CI]: −0.23 to −0.05, p = 0.002). After adjusting for age, sex, vascular risk factors, and APOE ε4 carrier status, the lowest mRNFL quintile group had a 64% higher dementia risk compared to the highest quintile (hazard ratio [HR] = 1.64, 95% CI: 1.17 to 2.30, p = 0.004). Each 5‐µm reduction in mRNFL thickness corresponded to a 15% increased risk (HR = 1.15, 95% CI: 1.02 to 1.30, p = 0.02), which remained significant after inverse probability weighting. Mediation analysis revealed that APOE pathways accounted for 7.6% (95% CI: 2.6% to 28.6%, p = 0.01) of the mRNFL‐dementia association. DISCUSSION Our findings resolve a controversy by showing that while APOE ε4 accelerates mRNFL degeneration, retinal imaging captures dementia‐related neuropathology through pathways distinct from direct APOE effects, solidifying its potential as an etiologically informative biomarker. Highlights The association between APOE ε4 carriers and thinner RNFL was solidified by the J‐T test and multiple linear regression, indicating genetic influence on retinal structure. After inverse probability weighting adjustment, each 5‐µm reduction in baseline RNFL thickness increased dementia risk by 15%, highlighting its long‐term predictive value. Only 7.6% of the effect of RNFL thickness on dementia risk was attributable to APOE status, underscoring the value of RNFL as a standalone, non‐invasive biomarker in the assessment of long‐term dementia risk.